The Normal Static Two-Point Discrimination in the Palmar Aspect of Hand in Adults and Children in a Sample Indian Population - K., S.K. Pandian; Thatte, M.R.; Agarwal, Pawan; Rajendran, S.; Ibrahim, Mohamed; Babu G, Vishnu; Madhavan, Latha; Sharma, A.N.; Ghanghurde, Bipin; Dugad, Anand; Kulkarni, Onkar; Shah, Harsh R.; Saraf, Mansi; B., Rajesh; Krishnamorthy, R.; Sridhar, K.; Bhat, Anil; Rao, Surya (Indian Journal of Plastic Surgery, 2024)
Background The normal ability to distinguish two points from one is known as the two-point discriminative (2PD) sense. This forms an extremely important assessment in patient with injuries to the nerves distributed to the upper extremity.Objective The aim of this study was to estimate the normal reference values of static 2PD in healthy adults and children.Materials and Methods A total of 624 normal adults comprising 380 men and 244 women were recruited randomly for the study at three different centers. Additionally, 172 healthy children, comprising 110 boys and 62 girls, were studied. Eight sensory areas in the palmar surface of the hand were delineated. The ability to distinguish the static 2PD was estimated in millimeters by using disk discriminator. The results were tabulated and statistically analyzed.Results The mean static 2PD in the adult population ranged from 2.78 to 3.5 mm in the fingertips and 5.39 to 7.13 mm in the mid-palm. There was a statistically significant difference between men and women in zones 6, 7, and 8. In children, the observed 2PD values were 2.15 to 3.63 mm in the fingertips and 4.10 to 5.77 mm in the palm. Children have a significantly better 2PD sense when compared with adults.Conclusion The normal value of static 2PD in the palmar surface of the hand among the Indian pediatric and adult populations was established in the study.
Keywords: static two-point discrimination; nerve injury; sensory assessment; disk discriminator normal value